Risiko Antisosial dan dengan Risiko Kecanduan Video Game Pada Remaja di SMAN 4 Yogyakarta - Ussi Khairani Frestiarizka; Carla Raymondalexas Marchira; Intansari Nurjannah (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2020)
Background: With the growing popularity of video games and concerns about their potential impact on youth behavior, study about the correlation between antisocial tendencies and video game addiction is crucial to be performed.Objective: This study examines the relationship between the risk of antisocial behavior and the risk of video game addiction among adolescents attending State Senior High School 4 in Yogyakarta.Method: This study employed an analytic correlational with a cross-sectional study design. Proportional random sampling was utilized, resulting in a sample size of 172 respondents. The Internet Gaming Disorder Scale-Short-Form (IGDS9-SF) and the Antisocial Process Screening Device were used to measure the two variables in this study. Due to the chi-square test not meeting the requirements, Fisher’s test was used as an alternative for data analysis.Result: Of the respondents, 19,8% exhibited tendencies towards antisocial behavior, while 1,2% indicated signs of video game addiction. Fisher’s test yielded a p value of 0,038 (p < 0,05). Conclusion: The findings reveal a significant correlation between the risk of antisocial behavior and the likelihood of video game addiction among the adolescents in this study.ABSTRAKLatar belakang: Dengan semakin populernya video game dan kekhawatiran tentang potensi dampaknya terhadap perilaku remaja, penelitian tentang hubungan antara kecenderungan antisosial dan kecanduan video game menjadi penting untuk dilakukan.Tujuan: Mengetahui hubungan risiko antisosial dan risiko kecanduan video game pada remaja di SMAN 4 Yogyakarta.Metode: Penelitian ini, merupakan penelitian analitik korelasional dengan rancangan penelitian cross-sectional. Random sampling proporsional digunakan dengan hasil 172 orang responden. Internet Gaming Disorder Scale-Short-Form (IGDS9-SF) dan Antisocial Process Screening Device digunakan untuk mengukur kedua variabel dalam penelitian ini. Karena uji chi square tidak memenuhi syarat, uji Fisher digunakan sebagai analisis data alternatif. Hasil: Sebanyak 19,8% responden menunjukkan kecenderungan antisosial, dan 1,2% menunjukkan risiko kecanduan video game. Uji Fisher memiliki nilai p value 0,038 (p < 0,05).Kesimpulan: Ada hubungan yang signifikan antara risiko perilaku antisosial dan risiko kecanduan video game di kalangan remaja.